Application of Structural Equation Model to Analyze Factors Affecting Financial Planning After Retirement - Khairi, M. Ihsan; Susanti, Dwi; Sukono, Sukono (iora, 2021)
Retirement is something that every working individual will experience. Retirement according to the Big Indonesian Dictionary (KBBI) is not working anymore because the term of office has finished. A person who has retired usually has the right to a pension fund. After retirement, the individual's income will decrease, but the necessities of life can increase. In order to still be able to meet the needs of life after retirement, it is necessary to have financial planning after retirement. There are several factors that influence financial planning after retirement, including income, attitude and culture. Income is an important issue in financial planning. One thing to consider carefully when planning for retirement and setting aside funds for that purpose is the estimate of the amount of money needed to have the expected quality of life in retirement. Attitude towards retirement planning is an internal psychological condition that is influenced by positive or negative assessments related to retirement planning. Cultural differences will result in different financial plans between individuals. In this study, the Structural Equation Model will be used to analyze the factors that influence financial planning after retirement for teachers in several schools in Tanah Datar Regency, West Sumatra. This study uses quantitative methods using a questionnaire as a data collection tool. Based on the collected questionnaires, simulations were carried out to obtain 170 data randomly. To facilitate data analysis, the AMOS application will be used. The results showed that these three factors had a significant effect on financial planning after retirement. The most influential factor on financial planning after retirement is culture with a parameter value of 0.639.